Pole pracy Misjonarzy Oblatów Maryi Niepokalanej na Cejlonie w XIX w. - KLUJ, WOJCIECH (Annales Missiologici Posnanienses, 2010)
The above presentation aimed at more specific analysis of the territory of the missionary work of oblates on Ceylon in the 19th century. On this base there will be possible to discuss more clearly forms, the scope and methods of the evangelizing work. Even though at the end of 19th century there existed in Ceylon five dioceses, from the perspective of the Oblate missions most convenient was to divide this presentation in two parts following the division of the island into the territory of the two apostolic vicariates existing in the time of the arrival of the Oblates to the island (Colombo and Jaffna). In both cases we analyzed districts and missions, where missionary posts were founded.